ANALISIS KUALITATIF DETERMINAN IMPLEMENTASI SENAM HAMIL DI PUSKESMAS DEPOK 2, KABUPATEN SLEMAN, DIY - Jacoba Nugrahaningtyas Wahjuning Utami; Tutik Astuti; Githa Andriani; Hana Decy (Medika Respati : Jurnal Ilmiah Kesehatan, 2021)
Qualitative Analysis Determinant Of Implementation Of Pregnant Gymnastics In Puskesmas Depok 2, Sleman Regency, DIYBackground: Pregnancy is a physiological process but can be pathological at any time. Pregnant gymnastics is a gymnastics that is done to prepare and train the muscles so that it can be utilized to function optimally in normal labor. Pregnant women are encouraged to do light exercise during pregnancy, so that the mother and fetus are healthier and will reduce problems that arise during pregnancy. Participation in pregnant gymnastics is influenced by several factors including knowledge, attitude, values, beliefs, policies, family support, morivasi, pregnant gymnastics infrastructure. Pregnant gymnastics has not been implemented directly in puskesmas. Objective: knowing what factors influence the implementation of pregnant gymnastics in Puskesmas Depok 2 Sleman Regency, DIY. Methods : the method used is qualitative research that explains the factors that influence the implementation of pregnant gymnastics in Puskesmas Depok 2. This research place is in Puskesmas Depok 1, Sleman, DIY, and data collection is conducted with in-depth interview techniques, the implementation of data collection in August - October 2020. Qualitative data processing is presented in narrative form. Results : the results of the study showed that determinants of the implementation of pregnant gymnastics include predisposition factors, supporting factors and driving factors for the implementation of pregnant gymnastics. Predisposition factors include knowledge, attitude, trust, values and beliefs, supporting factors include the availability of facilities and pre-facilities and policies puskesmas as a facility for the implementation of pregnant gymnastics, and driving factors include support from health centers, health workers and families. Conclusion : pregnant gymnastics activities in Puskesmas Depok II have not been held. Pregnant gymnastics is included in the activities in the Maternity Class program. If the class of pregnant women is held properly then the activities of Pregnant Gymnastics will be carried out properly. Influencing factors include knowledge, attitude, values, beliefs, motivation, policy support, infrastructure and support for husbands and or families